STRUKTUR MODAL PENDEKATAN DINAMIS PADA PERUSAHAAN PROPERTY, REAL ESTATE, DAN KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2018 - Ishak Ramli; Raleska; Henny (Jurnal Kontemporer Akuntansi, 2022)
The increase in business in the property sector, which each year does not have a significant impact, is suitable for observing the capital structure. The property sector is also considered to have a significant influence on the economic crisis. This study is intended to prove the effect of profitability, company size, liquidity, sales growth, nondebt tax shield, asset structure, optimal leverage and speed adjustment factors on capital structure. By using the financial statements of property companies for the years 2015-2018. Profitability data, company size, liquidity, sales growth, non-debt tax shield, and asset structure were analyzed using multiple regression to test their effect on capital structure, and optimal leverage and speed of adjustment data were analyzed using the Generalized Moment Method (GMM) to test. achieving optimal capital structure and speed of achieving optimal capital structure. The results found that firm size, liquidity, non-debt tax shield and speed of adjustment had a significant positive effect on capital structure, asset structure and optimal leverage had a significant negative effect on capital structure, while profitability and sales growth did not significantly affect capital structure.